Formulation of Pseudomonad Fluorescent as Plant Growth Promoting Rhizobacteria - Haqil Triyatdipa; Linda Advinda; Azwir Anhar; Dezi Handayani; Irdawati (Jurnal Serambi Biologi, 2023)
Plant growth promoting rhizobacteria, known as Plant Growth Promoting Rhizobacteria (PGPR), are bacteria found on the surface of plant roots and are beneficial microorganisms. Fluorescent pseudomonads are a group of bacteria belonging to PGPR and have the ability to dissolve phosphates, produce nitrogen, phosphorus, siderophores, and Indole Acetic Acid (IAA) to stimulate plant growth. PGPR must be immobilized in a certain carrier in the form of a formulation so that it is easy to use, store, commercialize, and apply to the field. Due to the increasingly expensive instant media, the development of media formulations continues to be carried out which can be organic or inorganic.